THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION, FAMILY ENVIRONMENT AND ENTREPRENEURIAL MOTIVATION ON ENTREPRENEURIAL STUDENT DECISIONS - Nugroho, Rifqi Maulana Adi; Fatimah, Feti; Wijayantini, Bayu (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
One of the driving factors for the growth of entrepreneurial spirit in a country lies in the role of universities through entrepreneurship education. Educational institutions, especially universities, support their students in increasing awareness of the importance of entrepreneurship. This study aims to determine and analyze the influence of entrepreneurship education, family environment and entrepreneurial motivation on entrepreneurial decisions of FEB students in the Management Study Program. This type of research uses a quantitative method with a sample size of 88 respondents and uses a Non-probability sampling technique with a purposive sampling technique using a data collection technique in the form of a questionnaire to respondents. The data analysis technique for this study uses instrument testing, classical assumptions, multiple linear regression, hypotheses and coefficients of determination. The results of the analysis obtained show that entrepreneurship education, family environment and entrepreneurial motivation have a positive and significant effect partially on entrepreneurial decisions, and have a simultaneous effect and the results of the R2 Determination Coefficient test with a contribution level of influence of 0.931 or 93%.